Confined and mined: anthropogenic river modification as a driver of flood risk change - Laura Quick; R. D. Williams; R. J. Boothroyd; T. B. Hoey; P. L. M. Tolentino; C. MacDonell; E. Guardian; J. Reyes; C. Sabillo; J. Perez; C. P. C. David (npj Natural Hazards)
Abstract Rivers are often confined by structures and subjected to aggregate mining. In dynamic rivers, these interventions cause changes to riverbed and bank topography that potentially cause changes in hydraulics and flood risk. Repeat, system-scale, high-resolution topographic surveys of the gravel-bed Bislak River, the Philippines, are used to quantify annual morphological change and, using two-dimensional hydraulic modelling, to simulate changes to flood risk. Aggregate mining exports sediment and creates pitted topography, and embankments cause both deeper channels and disconnect the river from its floodplain. The consequently increased channel capacity reduces flood risk, with up to a 5% decrease in inundated areas for 10- to 100-year return periods. Sediment deprivation also increases bed shear stress that can induce scour, infrastructure damage and increased flood impacts. Rising global floodplain populations and increasing demand for aggregate ensure that sustainably managing geomorphologically dynamic rivers to support floodplain development and mitigate flood impacts remains a pertinent challenge.